Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/nano11010112
|View full text |Cite
|
Sign up to set email alerts
|

Highly Porous Au–Pt Bimetallic Urchin-Like Nanocrystals for Efficient Electrochemical Methanol Oxidation

Abstract: Highly porous Au–Pt urchin-like bimetallic nanocrystals have been prepared by a one-pot wet-chemical synthesis method. The porosity of urchin-like bimetallic nanocrystals was controlled by amounts of hydrazine used as reductant. The prepared highly porous Au-Pt urchin-like nanocrystals were superior catalysts of electrochemical methanol oxidation due to high porosity and surface active sites by their unique morphology. This approach will pave the way for the design of bimetallic porous materials with unprecede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The demands for energy efficiency and environmental sustainability generated increasing interest in the fields of direct methanol fuel cells (DMFCs) on account of their high theoretical power density and long-term stability. Among state-of-the-art Pt-based electrocatalysts for fuel cells, Pt-based nanowires are considered to be the most active and promising. However, their commercial applications are restricted by the high price of Pt as well as performance degradation caused by agglomeration and accumulated carbonaceous intermediates (e.g., CO). , To improve the utilization rate and electrocatalytic performance of Pt-based catalysts, various strategies have been adopted to carefully design and prepare catalysts with specific compositions and structures. Among them, one-dimensional (1D) nanowires (NWs) have an ideal structure that facilitates electron conduction and reduces Ostwald ripening/aggregation compared to zero-dimensional (0D) nanoparticles (NPs). Moreover, the tenuous NWs form an expanded structure that effectively inhibits corrosion of the support and improves the durability of the electrocatalysts. , For example, Zhong’s group successfully synthesized the PtFe alloy twisty nanowire (TNW) catalysts by a simple hydrothermal method without surfactants. Due to this PtFe TNW structure and their bimetallic composition, the product displayed the highest activity and durability .…”
Section: Introductionmentioning
confidence: 99%
“…The demands for energy efficiency and environmental sustainability generated increasing interest in the fields of direct methanol fuel cells (DMFCs) on account of their high theoretical power density and long-term stability. Among state-of-the-art Pt-based electrocatalysts for fuel cells, Pt-based nanowires are considered to be the most active and promising. However, their commercial applications are restricted by the high price of Pt as well as performance degradation caused by agglomeration and accumulated carbonaceous intermediates (e.g., CO). , To improve the utilization rate and electrocatalytic performance of Pt-based catalysts, various strategies have been adopted to carefully design and prepare catalysts with specific compositions and structures. Among them, one-dimensional (1D) nanowires (NWs) have an ideal structure that facilitates electron conduction and reduces Ostwald ripening/aggregation compared to zero-dimensional (0D) nanoparticles (NPs). Moreover, the tenuous NWs form an expanded structure that effectively inhibits corrosion of the support and improves the durability of the electrocatalysts. , For example, Zhong’s group successfully synthesized the PtFe alloy twisty nanowire (TNW) catalysts by a simple hydrothermal method without surfactants. Due to this PtFe TNW structure and their bimetallic composition, the product displayed the highest activity and durability .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, researchers have begun to explore effective and efficient strategies to achieve the high dispersion of active substances, so as to optimize the use of noble metal resources [15]. The study found that the tunability of the microstructures and electronic states of active components on the atomic scale can provide higher performance for electrochemical reactions [20,21]. Unfortunately, it is still a difficult and challenging problem to improve the utilization rate of active components, the rate of catalytic reaction and the thermal stability of the catalyst by controlling the dispersion of active sites and the microstructure [22].…”
Section: Introductionmentioning
confidence: 99%